Decreasing water dependency for economic growth in water-scarce regions by focusing on water footprint and physical water: A case study of Xi'an, China. (October 2022) - Lu, Nan; Zhu, Jiwei; Tang, Zeming; Zhang, Jianmei; Chi, Hui
Abstract: Rapid economic growth has led to a surge in urban water consumption, making it imperative to reduce economic dependence on water resources to achieve sustainable urban development. This study selects Xi'an as the study area and adopts the Tapio decoupling model from the perspective of the integrating water footprint (WF) and physical water (PW) to measure the state and the stability of decoupling, and the LMDI method is introduced to decompose WF and PW into five drivers. The results show that: (1) Xi'an's water efficiency increased substantially from 48.05 CNY/m 3 in 2008 to 153.43 CNY/m 3 in 2018, but the urban water shortage remains a serious problem. (2) Water consumption and economic growth are generally decoupled weakly and strongly; compared with PW, WF has a stronger decoupling but is less stable. Agricultural decoupling is stronger than industrial decoupling; decoupling stability is higher for industrial PW, followed by agricultural WF, and lowest for agricultural PW. (3) Technology contributes significantly to the decoupling of PW and WF, while water-use efficiency and population size inhibit the decoupling, and these factors have a more significant impact on WF than PW. The study's findings can be used to formulate effective measures to promote sustainable urban development.